Comportamento do noni à salinidade da água de irrigação em solo com biofertilizante bovino - Souto, Antônio Gustavo de Luna; Cavalcante, Lourival Ferreira; Nascimento, José Adeilson Medeiros do; Mesquita, Francisco de Oliveira; Lima Neto, Antonio João de [UNESP] (My University, 2013)
Salt excess in soil and water used for irrigation can cause significant loss of production and growth in cultivated plants. Among some options for reduction of negative effects of salts to plants in cultivated areas, fermented bio fertilizer has been used to grow vegetables and fruit tree irrigated with saline water. The study aimed at evaluating the behavior of the noni plant to salinity of the irrigation water in substrate with and with no bio fertilizer. Treatments were arranged in a randomized block design with four replications, using a 5 × 2 factorial arrangement. Five levels of electrical conductivity of irrigation water (0.5, 1.5, 3.0, 4.5, 6.0 dS m-1) were used in substrates with and with no bio fertilizer. Parameters were evaluated as follows: plant height, stem diameter, number of leaves, leaf area, shoot dry matter and water consumption. All evaluated variables were negatively affected by the increase in salt concentration of the irrigation water, but always with less intense effects in treatments with bio fertilizer.The bio fertilizer does not eliminate, but mitigates the negative effects of salts in noni plants.
Behavior of noni plants (Morinda citrifolia L.) to salinity of irrigation water in soil with bovine biofertilizer
Keywords: Morinda citrifolia L.; Organic input; Salt stress